Transnational History and Colonial Records: Locating Bengali Mobility in the British Malaya - Gazi Mizanur Rahman (Journal of Maritime Studies and National Integration, 2019)
By the late 1980s, some historians began to identify their works as transnational history – which dealt with the past human mobility, and the circulation of goods, information, and ideas across the globe. Colonial records are an essential source for reconstructing transnational history. However, some of the colonial census-makers were not aware of the racial identity of transmigrants during the population enumeration. They categorised the transmigrants under different umbrella heads, and due to their stringent systems of cataloguing, the identity of diverse migrants was misplaced or generalised in census reports. Therefore, these certain ambiguities complicate the reconstruction of the transnational history of some specific migrant communities. With the impact of British colonialism in present-day South and Southeast Asia, South Asian multi-ethnic people, including Bengalis, migrated to Malaya. Initially, the British colonial administrators categorised the South Asian multi-racial migrants under different heads including “Bengalis & c.”, “Tamils & c.” and “Indians”. These umbrella terms in colonial records create problems in reconstructing the transnational history of anyone specific race from South Asia, such as the Bengali. Through a reinterpretation of colonial documents, empirical evidence, and oral interviews, this paper attempts to locate the Bengali migrants in British Malaya.